The impact of the COVID-19 pandemic on mental health - Budzyńska, Julia; Leśniewska, Magdalena; Kozioł, Ilona; Milanowska, Joanna (Journal of Education, Health and Sport, 2021)
BACKGROUND: The outbreak of a coronavirus pandemic in 2019 posed a serious threat to the global population. Coronavirus Disease 2019 (COVID-19) has not only been a public health emergency, but has also affected mental health worldwide. Patients were exposed to a number of significant stressors during COVID-19 infection by which it appears that it may have had a major impact on mental health. Little is known about changes in levels of psychological affect, stress, anxiety and depression during this pandemic. AIM OF THE STUDY: The purpose of this study was to analyze the most recent available literature on the association of pandemic COVID-19 with psychiatric disorders occurring both as a result of past infection and in response to stress associated with the new situation of a global epidemic of Sars-CoV-2 virus. RESULTS: The psychological effects of the epidemic are clearly noticeable. The study identified groups particularly vulnerable to developing symptoms of anxiety, depression and post-traumatic stress disorder. Risk factors were also identified in people working in health care as having direct contact with the effects of infection with the new virus. SUMMARY AND CONCLUSIONS: Key elements of preventing psychological impact are the creation of a mental health organization. Another important task for governments is to create the conditions for economic security, as financial problems or job losses can also be the cause of mental crises.